2019
DOI: 10.1080/21691401.2019.1666862
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin promotes rat hepatocyte proliferation both in vitro and in vivo

Abstract: Aim: This study aimed to examine the effects of osteopontin (OPN) on hepatocyte growth and liver regeneration (LR). Methods: A recombinant lentivirus expressing OPN and OPN-siRNAs were used to treat BRL-3A cells, while the adenovirus expressing OPN or OPN-targeted shRNA were applied for rat primary hepatocytes. Moreover, rrOPN and OPN-Ab were added to treat BRL-3A. Next, rrOPN was administrated into rat regenerating livers. Then in vitro and in vivo assays were performed to evaluate the biological function of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…A previous study using serum OPN to predict cancer risk in patients with COPD identified a rather small AUC value of 0.636 [33]. There are two forms of OPN, intracellular form (iOPN) and a secreted form (sOPN) [34], and sOPN may be produced by many cell types, including hepatocytes, cholangiocytes, hepatic stellate cells, macrophages, T lymphocytes and natural killer T cells [35]. A previous study demonstrated that the lungs produce plasma OPN [36]; however, plasma OPN may partly originate from the lungs in COPD and LC because many other cells are capable of producing OPN.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study using serum OPN to predict cancer risk in patients with COPD identified a rather small AUC value of 0.636 [33]. There are two forms of OPN, intracellular form (iOPN) and a secreted form (sOPN) [34], and sOPN may be produced by many cell types, including hepatocytes, cholangiocytes, hepatic stellate cells, macrophages, T lymphocytes and natural killer T cells [35]. A previous study demonstrated that the lungs produce plasma OPN [36]; however, plasma OPN may partly originate from the lungs in COPD and LC because many other cells are capable of producing OPN.…”
Section: Discussionmentioning
confidence: 99%
“… 35 Moreover, increased SPP1 was found to upregulate p‐STAT3, which activated STAT3 signalling in osteosarcoma and rat hepatocytes. 36 , 37 Here, we demonstrated that EEF2K regulates SPP1 in a STAT3‐dependent manner and p‐STAT3 binds to the promoter region of SPP1 to enhance its transcription.…”
Section: Discussionmentioning
confidence: 70%
“…Upregulation of OPN expression has been reported in hepatocellular carcinoma (HCC), where it promotes the proliferation and migration of HCC cells 14 . Inhibition of OPN leads to the suppression of cancer cell proliferation, as well as decreased regeneration and survival of primary hepatocytes, and cell cycle arrest 15 . Additionally, OPN has been implicated in the modulation of autophagy, where it attenuates fibrosis in atrial fibroblasts by inhibiting autophagy 16 .…”
Section: Introductionmentioning
confidence: 99%